The Influence of brand image, consumer perception, and E-WOM on purchase intentions for product X in DKI Jakarta - Richelle Valerie Tiofli; Rodhiah Rodhiah (Sultan Publisher, 2025)
This study looks at how customer perception, brand image, and electronic word-of-mouth (e-WOM) affect consumers' inclinations to buy products. This study used a quantitative methodology, and 120 respondents were given an online questionnaire to complete in order to gather data. These responders are customers who are knowledgeable about a certain product. Through the use of SmartPLS software, structural equation modeling, or SEM, was used to analyze the data. The study's findings indicate that purchase intention is significantly influenced by e-WOM, customer perception, and brand image. Brand image has been shown to have the most influence on customer purchase choices out of these three elements. There are useful ramifications for marketing tactics from this result. Therefore, in order to draw in more customers, it is critical for businesses to improve their brand image. Enhancing e-WOM and preserving favorable customer views are also essential for raising purchase intentions. It is thus believed that this study would help businesses create more successful marketing plans in cutthroat marketplaces.